1998
DOI: 10.1016/s0885-3924(98)00018-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Knowledge of Morphine for the Management of Cancer Pain

Abstract: Inadequate training of physicians contributes to the undertreatment of cancer pain. To address these concerns, the University of Kentucky has introduced a 4-week course for final-year medical students that teaches the principles of clinical pharmacology and pain management. The purposes of this study are to assess the knowledge deficits of final-year medical students about the use of morphine for cancer pain and to assess the efficacy of a short course on cancer pain management. Eighty-six final-year medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
2
22
0
2
Order By: Relevance
“…Even though it is one of the major fears related to the use of opioids in our study, the respondents reported that this situation is seldom experienced (incidence of 0.5%). This result is in consonance with other studies reporting that respiratory depression is a rare adverse effect, particularly when opioids are titrated for pain treatment [33,34].…”
Section: Barriers To Pain Treatmentsupporting
confidence: 91%
“…Even though it is one of the major fears related to the use of opioids in our study, the respondents reported that this situation is seldom experienced (incidence of 0.5%). This result is in consonance with other studies reporting that respiratory depression is a rare adverse effect, particularly when opioids are titrated for pain treatment [33,34].…”
Section: Barriers To Pain Treatmentsupporting
confidence: 91%
“…In the present study, pharmacology based items were the domain of weakest performance which is congruent with other international research studies who have also established that nurses illustrated the poorest knowledge and attitudes in the area of pharmacological aspects of pain and its management. High prescription rate of IM and PRN were demonstrated to be a sign of poor quality pain management (22,(28)(29)(30).…”
mentioning
confidence: 99%
“…28 The question with the 2nd most incorrect answer is the one on "Any patient given opioids for pain relief is at 25% or more risk for addiction," which is similar to the results reported by other investigators. 19,27 As most (86%) of the students either did not know the answer or agreed with the statement, it can be deduced that they continue to be concerned about addiction as an undesirable effect of opioid use. For this reason, it should be emphasized in succeeding lectures on cancer pain and pain management that psychological dependence is a very rare phenomenon in the palliative care population.…”
Section: Knowledge Scalementioning
confidence: 99%